KONSTRUKSI KAUSATIF BAHASA SERAWAI - Wisman Hadi (BAHAS, 2008)
Serawai Ethnic language causative construction in this paper is investigated through parameters of semantics and morphosyntactics. This construction is produced by combination of clause and conjunction ‘sebap’ or ‘kernau’; using analytic causative verb ‘nganuka’, ‘njadika’, ‘ngajung’, morphological causative affixes ‘-ka, ‘-i’, ‘ng-ka’, and ‘ng-i’ and using certain lexical choices in which have causative meaning. Konstruksi kausatif bahasa Serawai dapat dihasilkan melalui penggabungan klausa dengan konjungsi sebap/kernau, penggunaan kausatif analitik dengan verba nganuka, njadika, ngajung; penggunaan kausatif morfologis dengan afiks –ka, -i, ng-ka, dan ng-i; dan pemilihan verba kausatif leksikal tertentu yang sudah bermakna kausatif. Konstruksi kausatif BS dapat dijelaskan melalui parameter morfosintaksis dan parameter semantik